Respon Mainstream Terhadap Globalisasi dan Aplikasinya - Anam, Khoirul (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2016)
AbstractGlobalization as a multi-dimensional phenomenon at some point generate a variety of perspectives. On the one hand, the scientists assume that globalization is a science paradigrma (grand theory) in the scholarly community service, but if we look at the broader aspects of the globalization of the implications of globalization also posed on the pattern of development of science and technology world. Th is paper tries to elaborate the implications of globalization as an approach in the social sciences to the pattern of development of science and technology. In the early 1970s gold reached a stage of development of capitalism and technological development pattern at that time adopted many technological developments (hard technology) but when in the 1990s era of globalization comes the pattern of technological developments turn out to be more humane. What happens is that there is an attempt to force a culture to another culture. Th is will have a big impact on the life of society. Today, people fed to then make Western culture as daily until the new kemudian budaya releasing or removing people's identity. To overcome it, clearly need to be selective in accepting a culture.Keyword: globalization, technology, culture.